The reinforcement of NATO at the Eastern borders of the alliance and prospects for its expansion northward - A. Nikitin (Международная аналитика, 2016)
In the context of developing crisis in Russian-Western relations and as a reaction towards events in Ukraine the NATO undertakes significant and multi-dimensional increase of its military arsenals and contingents on the eastern borders of the Alliance. Measures of strengthening the military potential involve Baltic states, Poland, Romania, Bulgaria. Necessity to finally withdraw from limitations imposed by RussiaNATO Founding Act are under debates. Simultaneously involvement of northern neutral states (Sweden, Finland) into the Alliance is activated. At the same time, analysis of political statements of the leadership of northern neutral countries does not yet confirm their intention to refuse from neutral status.